2019
DOI: 10.3390/md17030187
|View full text |Cite
|
Sign up to set email alerts
|

Phytoene Accumulation in the Novel Microalga Chlorococcum sp. Using the Pigment Synthesis Inhibitor Fluridone

Abstract: Carotenoids are lipophilic pigments found in plants and algae, as well as some bacteria, archaea, and fungi that serve two functions—(1) as light harvesting molecules—primary carotenoids, and (2) as antioxidants, acting against reactive oxygen species–secondary carotenoids. Because of their strong antioxidant properties, they are also valuable for the development of anti-aging and photo-protective cosmetic applications. Of particular interest is the carotenoid phytoene, for its colorless and UV absorption char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…produce skincare substances that reduce the size of melanocytes and the amount of hyperpigmentation [170], halotolerant marine microalgae, such as Chaetoceros mulleri and Tisochrysis lutea, produce sterols used in the pharmaceutical industry [171], the pigment Astaxanthin successfully commercialized produced by Heamatococcus pluvialis [172], and Chlorococcum sp. produce carotenoids and phytoene [173]. Although there are some successful samples of microalgal cultures, some technologies can help to improve biomass are high-valuable compounds production, revalorize waste material by microalgal metabolism, and integrate a downstream process to obtain several products in one cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…produce skincare substances that reduce the size of melanocytes and the amount of hyperpigmentation [170], halotolerant marine microalgae, such as Chaetoceros mulleri and Tisochrysis lutea, produce sterols used in the pharmaceutical industry [171], the pigment Astaxanthin successfully commercialized produced by Heamatococcus pluvialis [172], and Chlorococcum sp. produce carotenoids and phytoene [173]. Although there are some successful samples of microalgal cultures, some technologies can help to improve biomass are high-valuable compounds production, revalorize waste material by microalgal metabolism, and integrate a downstream process to obtain several products in one cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that non-lethal doses of fluridone could lead to the accumulation of phytoene in Chlorococcum sp. The fatty acid composition in Chlorella also changed after fluridone treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorococcum sp. is known for accumulating large amounts of lipids [19] and producing high amounts of carotenoids [20]. Furthermore, Chlorococcum sp.…”
Section: Introductionmentioning
confidence: 99%